Serum 25 hydroxyvitamin D status in 6‐month‐old infants in Guangzhou, China: A paired longitudinal follow up study. Issue 2 (22nd January 2020) - Wang, Jing; Zhang, Joy Yue; Wei, Ru; Hu, Shunping; Lin, Tao; Lash, Gendie E.; Tan, Meizhen
Abstract: To assess the vitamin D status in healthy 6‐month‐old infants, as well as vitamin D supplementation and feeding patterns in Guangzhou, China, serum 25‐hydroxyvitamin D (25OHD) concentrations of 202 infants were measured at birth (cord blood) and at 6 months of age in Guangzhou, China. Questionnaires acquiring demographic characteristics, maternal and infantile vitamin D supplementation during pregnancy and first 6 months after birth, and feeding patterns during the first 6 months were completed by participating mothers. Physical examinations and blood sampling were carried out among infants at 6 months of age. The majority of infants (93.6%) were supplemented with vitamin D during the first 6 months of life on a voluntary basis. The M ± SD of cord serum 25OHD concentration was 46.2 ± 16.4 nmol/L, whereas the M ± SD of 25OHD concentration at 6 months was 82.9 ± 24.9 nmol/L. Serum 25OHD concentrations <30 nmol/L were seen in 34 (16.8%) infants at birth but only one (0.5%) at 6 months. Only 11 (5.4%) infants had concentrations >75 nmol/L at birth, whereas the majority of infants ( n = 131, 64.9%) had concentrations >75 nmol/L at 6 months. The main predictors of 25OHD levels at 6 months included season, vitamin D supplementation, parental education level, and feeding patterns. To conclude, serum 25OHD concentrations were low at birth in a southern Chinese population, and infantile supplementation is an effective way to improve 25OHD status. Exclusively breastfed infants might need greater vitamin D supplementation, and individualized vitamin D supplementation plans might be needed.